2022
DOI: 10.1302/0301-620x.104b8.bjj-2022-0074.r1
|View full text |Cite
|
Sign up to set email alerts
|

The Fragility Fracture Postoperative Mobilisation multicentre audit

Abstract: Aims The purpose of this study was to determine the weightbearing practice of operatively managed fragility fractures in the setting of publically funded health services in the UK and Ireland. Methods The Fragility Fracture Postoperative Mobilisation (FFPOM) multicentre audit included all patients aged 60 years and older undergoing surgery for a fragility fracture of the lower limb between 1 January 2019 and 30 June 2019, and 1 February 2021 and 14 March 2021. Fractures arising from high-energy transfer trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A recent national survey of weightbearing restrictions following lower limb fracture surgery found that only 13.7% of consultants allowed unrestricted weightbearing after surgical fixation of proximal tibial fractures in the elderly. 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent national survey of weightbearing restrictions following lower limb fracture surgery found that only 13.7% of consultants allowed unrestricted weightbearing after surgical fixation of proximal tibial fractures in the elderly. 26 …”
Section: Discussionmentioning
confidence: 99%
“…A recent national survey of weightbearing restrictions following lower limb fracture surgery found that only 13.7% of consultants allowed unrestricted weightbearing after surgical fixation of proximal tibial fractures in the elderly. 26 Limitations of this study include its retrospective nature. As examined and discussed, recalled prefracture scores likely overestimate baseline prefracture functioning and lead to bias when comparing against current scores.…”
Section: Variablementioning
confidence: 98%
“… 46 The treatment of geriatric fracture patients has evolved to encourage robust fixation or arthroplasty constructs to allow early weight-bearing and mobilization. 47 Several case series and small randomized controlled trials have examined the safety of early weight-bearing for geriatric distal femoral fracture patients and demonstrated that early weight-bearing can be considered appropriate for most patients. 48 , 49 A recent audit of fragility fracture management in the United Kingdom showed that 96% of patients with hip fracture were prescribed weight-bearing as tolerated after surgery, while only 32% of nonhip fracture patients were similarly prescribed full weight-bearing.…”
Section: Distal Femur Fractures: What Factors Determine Outcomes?mentioning
confidence: 99%
“… 48 , 49 A recent audit of fragility fracture management in the United Kingdom showed that 96% of patients with hip fracture were prescribed weight-bearing as tolerated after surgery, while only 32% of nonhip fracture patients were similarly prescribed full weight-bearing. 47 For patients with distal femur fracture, this varied based on the fixation method used and was noted to be 92% with arthroplasty treatment, 67% with use of an intramedullary nail, and 35% with plate fixation. Early mobilization and early surgery has been shown to reduce mortality rates in the elderly hip fracture population.…”
Section: Distal Femur Fractures: What Factors Determine Outcomes?mentioning
confidence: 99%
“…The British Orthopaedic Association proposed an even earlier timeframe of within 36 hours of admission [14]. Indeed, it is widely accepted that mobilising from bed early is essential for older adults to prevent complications of prolonged immobility, such as blood clots and pressure sores [15][16][17]. Restricted weight bearing may inhibit this early mobility as older adults with frailty may struggle to mobilise under partial-or non-weight bearing orders [18].…”
Section: Introductionmentioning
confidence: 99%